Village Asset Empowerment: Efforts to Increase Village Local Revenue - Shaleh, Khairul; Sukmawati, Fitri; Arwaty, Dini; Abbas, Sa’adah; Mulyawan, R. Ferry; Nababan, Daniel; Andriana, Nadila (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
This research aims to reveal the optimal empowerment of village assets to increase revenue. This research uses a qualitative descriptive approach, a research method to provide an objective description of the aim reality that occurs in a condition or environment. The data collection techniques were observation, in-depth interviews, literature study, and documentation. The data collection method led researchers to identify and understand the objective reality of the research location. The context of this research describes the utilization of assets owned by the village government to increase village revenue. The results show that in the context of certain village governments, there are indications that managing village assets still relies on administrative activities. The economic value potentially generated from assets could be more optimal because the focus of asset management is still limited to fulfilling administrative obligations. This research encourages that the management of village assets needs to be carried out intensively through asset empowerment schemes by third parties to provide economic value compensation for increasing village revenue.